A small molecule modulating monounsaturated fatty acids and Wnt signaling confers maintenance to induced pluripotent stem cells against endodermal differentiation - Hosseini, Vahid; Kalantary-Charvadeh, Ashkan; Hajikarami, Maryam; Fayyazpour, Parisa; Rahbarghazi, Reza; Totonchi, Mehdi; Darabi, Masoud (Stem cell research & therapy, 2021)
Stearoyl-coenzyme A desaturase 1 (SCD1) is required for de novo synthesis of fatty acids. Through the fatty acid acylation process, this enzyme orchestrates post-translational modifications to proteins involved in cell development and differentiation. In this study, we used biochemical methods, immunostaining, and covalent labeling to evaluate whether a small molecule modulating unsaturated fatty acids can influence the early endodermal differentiation of human-induced pluripotent stem cells (iPSCs).
Gesehen am 04.12.2021